Rheological and photophysical investigations of chromonic-like supramolecular mesophases formed by luminescent iridium(III) ionic complexes in water. Issue 5 (9th April 2017) - Rossi, Cesare Oliviero; Cretu, Carmen; Ricciardi, Loredana; Candreva, Angela; La Deda, Massimo; Aiello, Iolinda; Ghedini, Mauro; Szerb, Elisabeta Ildyko
ABSTRACT: Luminescent complexes with general formula [(C^N)2 Ir(N^N)]OCOCH3, where C^N = 2-phenylpyridine ( ppy ) and N^N = 2, 2ʹ-bipyridine ( bpy ), self-assemble into ordered 'soft' viscous mesophases of chromonic type. By changing the ancillary ligand with 1, 10-phenanthroline ( phen ), a new mesomorphic complex was obtained. The self-assembly into ordered liquid crystalline phases of chromonic type in water was investigated by comprehensive rheological and photophysical studies. By changing the ancillary ligand bpy with phen, assembly into smaller, more symetric aggregates is favoured, resulting in lower viscosity and more dynamic mesophase. Graphical Abstract: